One Year Reinductions with Vincristine, Asparaginase and Prednisone as Post-Remission Therapy Improves Outcome in Children with Intermediate Risk (IR) Acute Lymphoblastic Leukemia (ALL). - Albert Oriol; Pilar Bastida; Olga García; Carlota Calvo; Juan-Manuel Perez-Hurtado; Maria-Elvira González Valentin; Jose Luis Fuster; Izaskun Egurbide; Victoria Martin-Reina; Antonio Molines; Javier Lassaletta; Miguel-Angel Sanz; et al. (Blood, 2009)
Abstract Abstract 2026 Poster Board II-3 Background The ALL89 PETHEMA trial proved that delayed consolidation had a favorable influence on the outcome of children with IR-ALL.The subsequent ALL96 trial incorporated reinductions with vincristine, asparaginase and prednisone during the first year of maintenance therapy to the early and late consolidations of the previous protocol. We performed a historical comparison of both cohorts of children to evaluate the benefit of such approach in children with newly diagnosed ALL of low and intermediate risk in first complete remission. Methods Children aged 1 to 18 years were classified as low-risk (LR) if they were 1 to9 years of age and the WBC at diagnosis was < 50×10 9/l and as intermediate-risk (IR) if their age was >9 to 18 years or the WBC was > 50×10 9/l. High-risk patients [i.e. children with ALL carrying the t(9;22) or t(4;11) translocations or with WBC > 200×10 9/l] were excluded from analysis. The ALL89 trial assigned 213 with low (N=111) or intermediate (N=102) risk ALL in first complete remission to receive early or early and late consolidation cycles followed by 2 years of maintenance treatment with oral mercaptopurine and weekly intramuscular methotrexate. Children (86 IR and 233 LR) achieving CR in the ALL96 trial received similar early and delayed consolidations and additional monthly vincristine (2 mg IV), asparaginase (20000 UI/sq meter IV) and prednisone (60 mg/sq meter PO x 7 days) reinductions (VAP) were incorporated during the first year of maintenance treatment. The primary end point of the historical comparison was disease-free survival. Results Median follow-up of children in continuous first CR was 6 years (range 0.3 – 12). Patients in both trials were comparable in terms of gender, age, performance status and characteristics of ALL at diagnosis. 109 children (75 LR and 34 IR) in the ALL89 trial were assigned to receive early consolidation only (Cohort 1 – C1) and 104 (36 LR and 68 IR) to receive early and delayed consolidation treatment (Cohort 2 –C2). 281 children (79 LR and 202 IR) in the ALL96 trial received a median of 7 (range 3-7) reinductions with VAP after early and delayed consolidations (Cohort 3 - C3). 46 LR patients relapsed (24 in C1, 9 in C2 and 13 in C3). The 5-year disease-free survival rates were 67% (95%CI 58-76), 74% (95%CI 62-86) and 84% (95%CI 77-93) for C1, C2 and C3 respetively. The hazard ratios for patients in the C2 and C3 groups were 0.77 (95%CI 0.36-1.65, p=NS) and 0.45 (95%CI 0.22-0.93, p=0.031). 80 IR patients relapsed (18 in C1, 27 in C2 and 25 in C3). The 5-year disease-free survival rates were 46% (95%CI 31-61), 57% (95%CI 46-68) and 80% (95%CI 75-86) The hazard ratios for patients in the C2 and C3 groups were 0.77 (95%CI 0.42-1.39, p=NS) and 0.29 (95%CI 0.16-0.52, p